Impact of birth complications on breastfeeding duration: an internet survey. (5th July 2012) - Brown, Amy; Jordan, Sue
Abstract Aim To explore reasons underlying cessation of breastfeeding in mothers with uncomplicated vaginal deliveries and those experiencing complications during childbirth. Background Interventions during labour and childbirth can have a negative impact on breastfeeding. Explanations include adverse reactions to medication, delayed breastfeeding initiation, and disruption of the normal endocrinology of childbirth. However, reasons for breastfeeding cessation linked to birth experience have not been fully examined. Increasing breastfeeding duration and, consequently, improving infant and maternal health in the UK depend on understanding why women stop breastfeeding. Design An exploratory cross‐sectional survey. Method Between January–May 2009, 284 mothers attending community groups in Swansea, Wales, and mothers participating in online parenting forums, who initiated breastfeeding but discontinued before 6 months postpartum, reported their birth experience, including complications and reasons for breastfeeding cessation in an internet survey. Results Mothers who experienced birth complications breastfed for a significantly shorter duration than those who did not. Specifically, caesarean deliveries, foetal distress, failure to progress, and postpartum haemorrhage were each associated with a shorter breastfeeding duration. Mothers who experienced complications were more likely to discontinue breastfeeding for reasons of pain and difficulty than mothers who did not experience complications, yet no difference was seen between groups for social reasons such as embarrassment or a lack of support. Conclusion Certain complications during labour may increase risk of specific physical difficulties with breastfeeding, possibly due to their association with medications received. Maternity health professionals should be alert to this possibility to offer enhanced attention and care to overcome these issues and prolong breastfeeding duration.